Disposal of hexachlorodisilane and its hydrolyzed deposits. (May 2020) - Lin, Yu-Jhen; Nguyen, Thanh-Trung; Chin, Mo-Geng; Wang, Cheng-Chieh; Liu, Chien-Ho; Tsai, Hsiao-Yun; Chen, Jenq-Renn; Ngai, Eugene Y.; Ramachandran, Ram
Abstract: Hexachlorodisilane (Si2 Cl6, HCDS) is an important precursor used in semiconductor device manufacturing. It is a flammable as well as a water reactive liquid which hydrolyzes rapidly upon contact with water or moisture. The hydrolyzed deposits are also known to be shock-sensitive with explosion energy equivalent to trinitrotoluene (TNT). In this work, two phases of test program including disposal of HCDS and disposal of the shock sensitive HCDS hydrolyzed deposits were conducted. The first phase of the program was to find an agent that can completely dissolve/react the HCDS vapor without forming shock sensitive deposits. The second phase of the program attempted to find a suitable agent to suppress the Si–Si bonds, one of the essential roles of chemical functional groups in shock sensitivity of the HCDS hydrolyzed deposits to suppress the shock sensitivity. A variety of agents such as sulfuric acid solutions, aqueous sodium hydroxide (NaOH) solutions, aqueous potassium hydroxide (KOH) solutions, KOH/alcohol solutions were utilized as the suppressants in this work. Samples mixed with suppressants were not only tested for shock sensitivity by a Fall-hammer apparatus but also analyzed for chemical functional groups to identify the effect of each agent. Concentrated sulfuric acid was found to suppress the shock sensitivity of the liquid HCDS hydrolyzed deposits by acting as a medium that helps the hydrolyzed deposit to retain moisture. KOH/alcohol solutions can turn HCDS vapor into non-hazardous silica, so that, it provided a safe way to dispose HCDS. Finally, practical recommendations about handling and eliminating the risk of shock sensitivity are given for HCDS liquid spill, HCDS vapor vent and HCDS hydrolyzed deposits. Highlights: To find an agent to dissolve the HCDS vapor without forming shock sensitive deposits. To find an agent to suppress the shock sensitivity of the HCDS hydrolyzed deposits. To give practical recommendations about handling and eliminating shock sensitive deposits.